DEPRESSIVE SYMPTOMS IN PEOPLE WITH CHRONIC SPINAL CORD INJURY - Raelly Ramos Campos; Maira Di Ciero Miranda; Zuíla Maria de Figueireido Carvalho; Janaina Vall (Universidade Federal do Paraná, 2013)
Changes in mood indicative of a depressive state are common in persons with spinal cord injuries, principally in those cases where the disability is permanent. This cross-sectional study was undertaken in 2012, in Fortaleza-Ceará, with 35 patients with traumatic spinal cord injuries, and through applying the Scale for Populational Screening for Depression with the aim of evaluating the occurrence of depressive symptoms. Among the participants, 91.43% were paraplegics and in 37.14% the etiology of the spinal cord injury was a gunshot wound. In relation to the depressive symptoms, 48.57% of the participants showed an absence of symptoms; 22.86% had mild to moderate depression and 28.57% had serious depression. It is concluded that depression is frequent in those with chronic traumatic spinal cord injuries; the Screening Scale is simple to use and has good sensitivity for the detection of depressive disorder in these patients.